Spirometry Results in Children over Five Years Old with COVID-19 at Least Six Months after Discharge - Mahsa Ashtari-Nejad; Mehran Karimi; Farzad Ferdosian; Farimah Shamsi; Abdolhamid Jafari Nodoushan (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Since it is necessary to detect changes in lung function for the follow-up of the patients with respiratory and functional complications caused by COVID-19, in this study, we decided to examine the results of spirometry in children over 5 years old with Covid-19. Methods: In this cross-sectional study, 52 over-five-year-old children, hospitalized due to COVID-19 for at least six past months, were examined. The participants’ demographic information, respiratory symptoms, underlying diseases, severity of COVID-19 according to WHO, severity of lung involvement in CT scan, type of lung involvement, oxygen saturation at admission as well as FEV1, FVC, and FEV1/FVC were collected and analyzed, the results were analyzed using SPSS version 16 software and t-test and Chi-square tests. Results: Of all investigated patients،, 26 were boys (50%) and 38 (73.1%) were 5-12 years old. The minimum age of the children was 5 years and the maximum was 18 years. The mean age of children was 3.41±10 years. The FEV1/FVC ranged from 61% to 79% in five patients (9.6%) and from 80% to 100% in 47 patients (90.4%). The FEV1 was lower than 80% in 28 and higher than 80% in 24 patients. FEV1/FVC had no significant relationship with the participants’ age, gender, clinical manifestations, and disease severity in terms of pulmonary involvement, but it had a significant association with blood oxygen saturation level (P: 0.001). Conclusion: The changes in pulmonary function tests vary in different months following contamination with COVID-19. In the present study, 9% of the patients, who were examined in the sixth month after infection, had abnormal pulmonary function test results. Based on the findings, the pulmonary function test results had no significant relationship with the patients’ age, gender, and clinical symptoms, while it was significantly associated with their blood oxygen saturation intensity.